Dialog. Ján Kudlička. Rastislav Biarinec - Gažíková, Zuzana; Ľuptáková, Eva, 1956-; Lajčiak, Ladislav, 1945- (Galéria P. M. Bohúňa, 2003)
Galéria P.M.Bohúňa, Liptovský Mikuláš Oravská galéria, Dolný Kubín Turčianska galéria, Martin